Training with virtual learning environments for industrial refrigeration systems. - Yanchapanta Yánez, Fernanda Elizabeth (2019)
This article describes an application for the training of engineering students and industrial refrigeration plants, based on virtual learning environments. The application developed in the Unity 3D engine allows the interaction and immersion user and environment; through the modeling of a cooling system by steam compression, the inclusion of disturbances using Matlab software that allows the manipulation of dependent variables to have a more realistic background in combination with the bilateral communication TCP. IP protocol. The exchange of information in real time between the two programs is essential because feedback between user and environment is needed, the user manipulates the system while updating its parameters according to the thermodynamic variables evaluated by Matlab. The application presents three training modalities, i) Pedagogical scene: conventional refrigeration module, ii) Industrial scene: real refrigeration installation, and iii) Failure mode; in order to relate the environments and integrate the user for that improve competencies and skills through the manipulation, supervision, and operation of processes. The result of this study is a virtual application based on the characteristics of virtual learning environments. Finally, the virtual application is validated with respect to a real one, disturbances influence the performance of the system is analyzed and the interaction with the environment is tested.